PENGARUH HERBISIDA OKSADIAZON 250 G/L TERHADAP PENGENDALIAN GULMA, PERTUMBUHAN DAN HASIL TANAMAN PADI SAWAH (Oryza sativa L.) - Nugraha, Dadan Ramdani; Wijaya, Acep Atma; Wiguna, Nugie Noermaula; Widaya, Dedi (Percetakan Umi Toaha Makassar, 2024)
Weeds are plants that have a negative value, grow spontaneously, and can compete with rice plants because they have the same root system, causing competition for water, nutrients, carbon dioxide, and sunlight. This study aims to determine the effectiveness of Oxadiazon 250 g/l herbicide on weed control and its effect on the growth and yield of lowland rice plants. This research was conducted in Palasah Village, Kertajati District, Majalengka Regency, West Java. The experiment was conducted using a non-factorial Randomized Block design (RBD) with seven treatments and four replications. The experiment consisted of 5 treatments of Oxadiazon 250 g/l herbicide with doses of 1.00 l/ha, 1.50 l/ha, 2.00 l/ha, 2.50 l/ha, and 3.00 l/ha with manual weeding and control treatments as comparison). If there is a significant difference in the data obtained, it will be further tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the application of the herbicide Oxadiazon 250 g/l at a dose of 2.00 – 3.00 l/ha was able to suppress the growth of broadleaf weeds (Spenochloa zeylanica, Ludwigia octovalvis and Marsilea crenata), sedge weeds (Fimbristylis miliacea and Cyperus iria) and grass weeds (Leptochloa chinensis).